Reflections on Binary Sex/Gender Categorization in Magnetic Resonance Tomography and its Future Challenges - Fitsch, Hannah (Frontiers in Sociology, 2021)
This paper examines the role of technical, methodological conditions in functional magnetic imaging (fMRI) in the production of binary sex/gender differences. The aim is to investigate the scanning process and shifts the focus to the statistical parameter of gendered markers within, which are currently reproduced and reapplied by using gendered data in computer models and big data studies. It discusses empirical methodologies and epistemic underpinnings of differentiation through statistics and argues that counter-counting, weighing and sizing might not help to substantiate the idea of ‘equality’ (not only for the sex/gender category) in brain studies. Referring to the topic of this special issue, I argue that for an interdisciplinary approach to criticize dimorphism and differentiation by groups, a wider understanding of the technical and theoretical foundations used in brain research is needed.